APPLICATION OF SECURITY & COMFORT CONCEPTS IN THE TRADITIONAL SILIMO SETTLEMENT IN THE BALIEM VALLEY - Salipu, M. Amir; Santoso, Imam Santoso2 (Border: Jurnal Arsitektur, 2023)
The tribal war culture is very closely related to the location selection and building mass layout of the Hubula Tribe Silimo settlement. In addition, the shape of the Pilamo and Ebe-ai buildings in the Silimo settlement reflects the concept of safety and comfort. The problem of this research is how the arrangement of building masses with the concept of building mass layout in the Silimo settlement can embody a symbol of security. What are the functions and meanings of building forms, spatial planning and social relations as a symbol of comfort in the Silimo settlement. The method used to answer research problems is a qualitative research method with a phenomenological approach. The results achieved by this study are how a security-based theoretical study can explain the selection of location, building layout and building form in the Silimo Hubula settlement in the Baliem Valley based on the concept of defensible space which includes: territoriality, natural surveillance, image and milieu, and Environment. Comfort in the form of relief, ease, transcendence related to the following aspects: Selection of location, material and shape of the building; Space organization with extended family concept; and space privacy.